The Use of Oseltamivir as Adjunctive Therapy for the Treatment of Hand-Food-and-Mouth Disease: A Meta-Analysis of Randomized Clinical Trials - Zhao, Yijing; Sun, Yangyang; Alolga, Raphael N.; Ma, Gaoxiang; Wang, Fan (Frontiers in Pharmacology, 2021)
Hand-foot-and-mouth disease (HFMD) is a common childhood illness caused by enteroviruses. Oseltamivir (OS), a neuraminidase inhibitor, has been frequently used as an adjunctive therapy for the treatment of HFMD. Solid evidence, however, is lacking regarding the efficacy of such adjunctive therapy. This work is to conduct a meta-analysis of randomized clinical trials (RCTs) to assess the efficacy of oseltamivir for HFMD in children. Eligible studies from inception to 10th October 2020 were identified by searching six databases (PubMed, Embase, CENTRAL, CNKI, Wanfang, and VIP database). Quality of evidence was assessed using the Cochrane Collaboration tool.Of a total of 91 entries, 11 RCTs involving 977 HFMD children were included in the final analysis. The results showed that the therapy combined with oseltamivir was more effective, with higher effective rate (RR, 0.84; 95% CI, 0.80 to 0.87; p < 0.01), shorter fever clearance time (days) (SMD, -0.74; 95%CI, -1.12 to -0.35; p < 0.01), shorter rash regression time (days) (MD, -0.89; 95%CI, -1.05 to -0.72; p < 0.01) and shorter clinical cure time (SMD, -1.08; 95%CI, -1.55 to -0.61; p < 0.01). No significant difference was observed in the risk of adverse reactions between the groups with and without oseltamivir.The use of oseltamivir as adjunctive therapy shows effectiveness and no increased risk of adverse reactions for the treatment of HFMD in children.